Overcoming inefficiencies in patent licensing: A method to assess patent essentiality for technical standards - Bekkers, Rudi; Tur, Elena M.; Henkel, Joachim; van der Vorst, Tommy; Driesse, Menno; Contreras, Jorge L. (Research Policy, 2022)
The market for patent licenses, despite its paramount importance for technological innovation, has various inefficiencies. A particular problem with widely used technical standards such as LTE and Wi-Fi is the lack of information regarding which patents are “essential” to implement the standard. This information is crucial because it simplifies determining infringement and implies specific “FRAND” licensing rules. While many standards-developing organizations stipulate that such patents are explicitly declared, little is known about which are actually essential. The absence of publicly available information on essentiality incurs significant social costs due to the resulting friction in the licensing market. With the growing use and importance of standards to mobility and energy markets, and to the Internet of Things, these costs are likely to rise. Responding to calls from industry, courts and policymakers, commercial and academic studies have attempted to assess essentiality, but they all have limitations. This paper reports on the technical feasibility of a system of expert assessments for patent essentiality. Based on a factorial design, we conducted a field experiment with 20 patent examiners performing over 100 assessments. Comparing the outcomes to a high-quality reference point shows that sufficiently accurate expert assessments, at a price level that allows large scale testing, are technically feasible, and we identify routes to further improvement.